Tissue screening after breast reduction. (10th March 2009) - Keshtgar, Mohammed; Jahromi, Alireza Hamidian; Davidson, Tim; Escobar, Paula; Mallucci, Patrick; Mosahebi, Afshin; Baum, Michael
Abstract : Patients who undergo breast reduction surgery have a low risk of being found to have breast cancer, but they need to be made aware of it—and doctors need to debate whether routine histological examination of tissue specimens is a good idea. We sought the views of Tom Treasure, a surgeon (doi:10.1136/bmj.b759 ), Jeremy Sugarman, an ethicist (doi:10.1136/bmj.b753 ), and Tessa Boase, a lay person (10.1136/bmj.b776 )